DECISION SUPPORT SYSTEM FOR RECEIVING PKH ASSISTANCE USING THE SAW AND WP METHODS - Husaeni; Siti Mukodimah; Ferry Susanto (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Poverty in Indonesia is very concerning, therefore the government created an assistance program for poor families, namely PKH , to help determine in determining someone who is eligible to receive this assistance in Bagelen Village, a decision support system is needed because it can minimize the occurrence of errors in determining in selecting residents who wish to get PKH assistance , therefore the purpose of this research is to reduce the wrong target in making decisions in providing PKH assistance . Because there are still many decision-making errors in the provision of program assistance, Bagelen Village, Gedong Tatataan District, Pesawaran Regency, Lampung is one of the villages designated as beneficiary families whose components include school children, toddlers, pregnant women, the elderly, and those with severe disabilities. This program requires that Very Poor Households (RTSM) can follow the requirements set by the government in the program. The requirements are sending their children to education, as well as carrying out routine visits to health facilities for toddlers and pregnant women. From visits to several families receiving the PKH Program, families who receive this assistance can be said to meet the criteria desired by the Indonesian government. From PKH assistance recipients, valid data or definite data will be obtained and will soon be taken care of by the local village government. It is hoped that the data obtained can be used properly and correctly according to the needs of the families receiving PKH assistance. The author uses the SAW and WP methods to get or select which poor families are entitled to this assistance because the SAW and WP methods can calculate more easily, quickly , and precisely, can be calculated manually as well as computer systems, using these two methods requires criteria for conduct an assessment, and the final result of the SAW and WP methods is to determine whether or not the PKH beneficiary is eligible or not based on the results of the calculations of the two methods.